2007
DOI: 10.1051/0004-6361:20066165
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic modelling of disk galaxies

Abstract: This is the second of a series of papers in which the kinematics of disk galaxies is studied by analysing spectroscopic data. Making use of the methods presented in Paper I, this work focuses on the large-scale distribution of disk and Dark Matter halo material by analysing the structure of warped galaxies. H i observations of three disk galaxies showing regular large-scale ("grand-design") warps are presented and their structure is analysed. The kinematics and geometry of the galaxies are modelled by fitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…Kandalian & Kalloghlian (1998), Chapelon et al (1999) and Cabrera-Lavers & Garzón (2004) found evidence of a central isophotal distortion that they explain postulating the existence of a bar with diameter of 38 . Other authors did not confirm the presence of a bar in UGC 4284, nevertheless they encountered non-circular and off-plane gas motion in the inner region of UGC 4284 that they discuss as originated by a warped gaseous disk (Coccato et al 2004;Józsa 2007). Bearing in mind the purpose of the present study it is important to determine which kind of baryonic components do actually exist for UGC 4284, and given the incongruity of the above reported results we required to perform 2D isophotal analysis of the surface brightness of this galaxy, using GAL-FIT (Peng et al 2002(Peng et al , 2010) and considering at least three principal components: disk, bulge and bar.…”
Section: D Galfit Disk/bulge/bar Decomposition Of Ugc 4284mentioning
confidence: 97%
“…Kandalian & Kalloghlian (1998), Chapelon et al (1999) and Cabrera-Lavers & Garzón (2004) found evidence of a central isophotal distortion that they explain postulating the existence of a bar with diameter of 38 . Other authors did not confirm the presence of a bar in UGC 4284, nevertheless they encountered non-circular and off-plane gas motion in the inner region of UGC 4284 that they discuss as originated by a warped gaseous disk (Coccato et al 2004;Józsa 2007). Bearing in mind the purpose of the present study it is important to determine which kind of baryonic components do actually exist for UGC 4284, and given the incongruity of the above reported results we required to perform 2D isophotal analysis of the surface brightness of this galaxy, using GAL-FIT (Peng et al 2002(Peng et al , 2010) and considering at least three principal components: disk, bulge and bar.…”
Section: D Galfit Disk/bulge/bar Decomposition Of Ugc 4284mentioning
confidence: 97%
“…Indeed, Van der Kruit (2007) points out that often rotation curves show a sharp decline at the onset of the warp, while he explains this feature with a drop in the mass-surface density of the stellar disk. However, Józsa (2007) observes a distinct increase of the rotation velocity in the warped region in a sample of three disk galaxies, which certainly cannot be explained by a drop in the stellar surface-mass density. In M33, a similar increase at the onset of the warp is observed (Corbelli & Schneider 1997).…”
Section: Observational Evidence For Infall Of Matter In Warped Galaxiesmentioning
confidence: 76%
“…Indeed, it has been remarked that anomalous gas is observed in warped disks. Józsa (2007) finds anomalous gas to be present in three galaxies selected to show a prototype symmetric warp. Certainly, these findings do not allow to draw a direct connection of warping properties of galaxies and the existence of anomalous gas.…”
Section: Observational Evidence For Infall Of Matter In Warped Galaxiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Some evidence for lagging, extraplanar gas in low-mass galaxies (NGC 2541, NGC 5204, UGC 3580) has been found by Józsa (2007). Kamphuis et al (2011) stated in a more detailed study of the H  structure of the dIrr UGC 1281 that a definite conclusion is not possible for UGC 1281 and that a faceon warp of the disk could reproduce the data as well as slowly rotating extraplanar gas, a lagging disk.…”
Section: Introductionmentioning
confidence: 97%